THE ROLE OF GOVERNMENT IN REVITALIZATION OF ISLAMIC SCHOOL IN TURKEY - Raharjo Raharjo (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
Islam had been the religion of the state in Turkey for many centuries, but it was disappeared when the type of the state was changed into republic in 1923. Turkey then has become a secular state and Islam has been depressed. However, when the political system in Turkey adopted multiparty and the party supported by Muslim community run the ruling government, Islam gradually has existed. This affected the Islamic education and schools, which have been sharply increased in number during the last 2 decades. This research was conducted to identify the quality control of education, the types of Islamic education and the role of government towards Islamic schools. By using techniques of documentation, observation and interview, this research indicated that: 1) the quality control of education in Turkey is done under ministry of national education; 2) the types of Islamic education are divided into public and private and  3) the role of government towards Islamic schools is not implemented straight forward, but through the policy in the Ministry of National Education addressed towards the public schools.